2009
DOI: 10.1073/pnas.0812885106
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of limiting-CO 2 –induced gene HLA3 decreases HCO 3 transport and photosynthetic Ci affinity in Chlamydomonas reinhardtii

Abstract: The CO2-concentrating mechanism (CCM) of Chlamydomonas reinhardtii and other microalgal species is essential for photosynthetic growth in most natural settings. A great deal has been learned regarding the CCM in cyanobacteria, including identification of inorganic carbon (Ci; CO 2 and HCO 3 ؊ ) transporters; however, ABC transporter ͉ CO2-concentrating mechanism ͉ microalgae ͉ RNAi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
98
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 32 publications
4
98
1
Order By: Relevance
“…It is also clear, however, that even though it is dispensable, LCIB contributes to viability in very low CO 2 (Duanmu et al, 2009a), although neither its level of contribution to nor its precise role in Ci uptake under these conditions has been established. Two putative Ci transporters have been demonstrated to contribute LCIBindependent Ci uptake in C. reinhardtii .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is also clear, however, that even though it is dispensable, LCIB contributes to viability in very low CO 2 (Duanmu et al, 2009a), although neither its level of contribution to nor its precise role in Ci uptake under these conditions has been established. Two putative Ci transporters have been demonstrated to contribute LCIBindependent Ci uptake in C. reinhardtii .…”
mentioning
confidence: 99%
“…Two putative Ci transporters have been demonstrated to contribute LCIBindependent Ci uptake in C. reinhardtii . Knockdown of HLA3, a gene encoding an ATP-binding cassette transporter protein, causes growth defects in LCIB mutants in very low CO 2 and decreased Ci accumulation especially at a high pH (Duanmu et al, 2009a). HLA3 is predicted to be localized on the plasma membrane, and therefore is very likely involved in HCO 3 2 transport at this location.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another report suggested the close participation of CO 2 in inorganic nitrogen assimilation (for review, see Fernández et al, 2009). LCIA, or NAR1.2, is involved in the bicarbonate transport system in chloroplasts (Duanmu et al, 2009) but is not regulated by nitrogen availability, and has been identified as a low-CO 2 -inducible gene by expressed sequence tag (EST) analysis . However, NAR1 genes generally involve members of the formate/nitrite transporter family (Rexach et al, 2000).…”
Section: Molecular Mechanisms For High-co 2 Responsesmentioning
confidence: 99%
“…Dissolved inorganic carbon and nitrogen species drawn in bold dominate. CA, carbonic anhydrases; CA2, CAH2 Rawat & Moroney, 1991;Tachiki et al, 1992); NiR, nitrite reductase; NR, nitrate reductase; PG, 2-phosphoglycolate; PGA, 3-phosphoglycerate; PSII, photosystem II; Rh, Rh1 (Soupene et al, 2002;Yoshihara et al, 2008); T, (putative) transporters; Ta, LCIA (Duanmu et al, 2009;Mariscal et al, 2006); Tb, HANT/HANiT system IV (Galván et al, 1996;Rexach et al, 1999). CCM models of WT/LC cells, inorganic nitrogen assimilation, and photorespiratory carbon oxidation in C. reinhardtii are modified from Yamano et al (2010), Fernández et al (2009, and Spalding (2009), respectively.…”
Section: Molecular Mechanisms For High-co 2 Responsesmentioning
confidence: 99%